Atypical Presentations of Sinonasal Inverted Papilloma: Surgical Management and Influence on the Recurrence Rate. Issue 2 (March 2016) - Akkari, Mohamed; Lassave, Jérome; Mura, Thibault; Gascou, Grégory; Pierre, Guillemette; Cartier, César; Garrel, Renaud; Crampette, Louis
Background: Sinonasal inverted papilloma (SNIP), classically, is a unilateral benign tumor of the nasal lateral wall. Numerous variations have been observed, depending on location, bilateral presentation, or association with nasal polyposis. Objective: The aim of this work was to describe atypical presentations of SNIPs with their management specificities and to assess their influence on the recurrence rate in a large case series. Methods: A retrospective single center study of 110 patients treated for SNIP. Atypical inverted papillomas were identified according to the following criteria: (1) unusual location (frontal, posterior, anterior), (2) bilateral involvement, and (3) association with nasal polyposis. Surgical management was detailed, and the influence of each atypical group on recurrence was assessed by using Kaplan-Meier survival curves and the log-rank test. Results: Distribution of atypical presentations was as follows: frontal sinus localization (10.9%); posterior localization, including sphenoid sinus (9%); nasal anterior localization (3.6%); bilateral involvement (3.6%); and nasal polyposis association (10%). The surgical approach was endoscopic (74.5%), external (5.5%), or combined endoscopic and external (20%). Except for nasal anterior localization, all the groups were associated with a higher recurrence rate, without reaching statistical significance. Conclusion: Recurrence rates for these atypical presentations arise from their specific surgical challenges. The choice of the surgical technique is guided by tumor location and extension, and by the surgeon's experience; the main objective is a complete resection. The endoscopic endonasal approach is the most frequent procedure.